2012
DOI: 10.5194/amt-5-1319-2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and mitigation of the impact of scene inhomogeneity on Sentinel-4 UVN UV-VIS retrievals

Abstract: Abstract. The quality of trace gas products derived from measurements of a space-borne imaging spectrometer is affected by the inhomogeneity of the illumination of the instrument slit and thus by the heterogeneity of the observed scene. This paper aims to quantify this effect and summarise findings on how to mitigate the impact of inhomogeneous slit illumination on tropospheric O 3 , NO 2 , SO 2 and HCHO columns derived from measurements of the Sentinel-4 UVN imaging spectrometer. For this purpose, spectra for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In space, however, the instrument slit will be illuminated inhomogeneously due to ground scene heterogeneities on scales smaller than the instrument's field of view. Inhomogeneous illumination across the slit leads to a distortion of the ISRF as described by Noël et al (2012), Caron et al (2014) and Landgraf et al (2016), and it can affect the retrieval accuracy of the TROPOMI methane product. Small-scale heterogeneities of the ground scene are generally caused by spatial variations of surface reflection and by broken clouds.…”
Section: Heterogenous Slit Illuminationmentioning
confidence: 99%
“…In space, however, the instrument slit will be illuminated inhomogeneously due to ground scene heterogeneities on scales smaller than the instrument's field of view. Inhomogeneous illumination across the slit leads to a distortion of the ISRF as described by Noël et al (2012), Caron et al (2014) and Landgraf et al (2016), and it can affect the retrieval accuracy of the TROPOMI methane product. Small-scale heterogeneities of the ground scene are generally caused by spatial variations of surface reflection and by broken clouds.…”
Section: Heterogenous Slit Illuminationmentioning
confidence: 99%
“…However, the retrieval using standard Gaussian slit functions shows the smallest variations of biases and variations of residual RMS, which is not fully understood. It is possible that the slit function in radiance measurements cannot be fully represented by the on-orbit slit functions derived from the solar irradiance due to scene inhomogeneity Noël et al, 2012), unaccounted stray lights, or intra-orbit slit function changes (observed in GOME-2 by Beirle et al, 2017) in earthshine spectra.…”
Section: Impact Of Slit Functions On Ozone-profile Retrievalmentioning
confidence: 99%
“…It should also be noted from Noël et al (2012) that the distortion of the slit function for an inhomogeneously illuminated slit could also be another reason for the difference in retrieval performance [38].…”
Section: Scoping Studymentioning
confidence: 99%